Tax Incentives for Innovative Activities - Duravkin, P. (НДІ ПЗІР НАПрН України, 2022)
Innovative activity is always a powerful driver of social and economic development of any state. At the same time, research and development also needs a certain amount of nourishment, first of all, from the state, in particular through the appropriate regulatory and legal mechanisms for its incentive. And the more the state is interested in scientific and technical development, the wider the circle should be and the more perfect the mechanisms for incentive innovative activity should be. The purpose of this article is to analyze the norms of the current regulatory legal acts of Ukraine, which provide for tax benefits in connection with the implementation of innovative activities, as well as to compare them with tax preferences in some countries of the European Union. Thus, the procedure for providing tax relief for funds received from the Innovation Development Fund (Ukrainian Startup Fund) has been analyzed. The elements of the legal mechanism for granting this benefit are singled out and characterized, its impact on the object and tax base is determined, and the circle of taxpayers to whom it applies is outlined. The legal status of the Ukrainian Startup Fund, the order and scope of its financing from the state budget have been determined. Attention was also paid to determining the essence and features of the provision of budget grants, their impact on the incentive of innovative activity. The elements of the tax-legal mechanism for providing budget grants are characterized, their impact on the object and tax base is indicated, and the categories of taxpayers who are entitled to a tax benefit in connection with receiving a budget grant are established. It is emphasized that today tax benefits apply only to budget grants provided by the Ukrainian Cultural Fund. In turn, on the basis of the analysis of the works of scientists from legal and economic sciences, a list of the most common tax benefits used to incentive innovative activity was determined in global practice. Particular attention is paid to the peculiarities of tax incentives for innovative activity in Poland, Hungary, Spain and France. Common features and fundamental differences between the concepts of tax and legal incentives of innovative activity in Ukraine and in the specified countries of the European Union have been established. Інноваційна діяльність завжди виступає надпотужним провідником соціально-економічного розвитку будь-якої країни. У той же час, науково-дослідна та дослідно-конструкторська робота також потребує певного живлення, в першу чергу, з боку держави, зокрема через відповідні нормативно-правові механізми її стимулювання. І чим більше держава зацікавлена у науково-технічному розвитку, тим ширшим має бути коло та тим більш досконалими мають бути механізми стимулювання інноваційної діяльності. Метою цієї статті є аналіз норм чинних нормативно-правових актів України, які передбачають податкові пільги у зв’язку із здійсненням інноваційної діяльності, а також порівняння їх із податковими преференціями у деяких країнах Європейського Союзу. Так, проаналізовано порядок надання податкової пільги щодо коштів, які отримуються від Фонду розвитку інновацій (Українського фонду стартапів). Виокремлено та дано характеристику елементам правового механізму надання цієї пільги, визначено її вплив на об’єкт і базу оподаткування, а також окреслено коло платників податків, яких вона стосується. Визначено правовий статус Українського фонду стартапів, порядок та обсяг його фінансування за рахунок коштів державного бюджету. Також приділено увагу визначенню сутності та особливостей надання бюджетних грантів, їх впливу на стимулювання інноваційної діяльності. Охарактеризовано елементи податково-правового механізму надання бюджетних грантів, позначено їх вплив на об’єкт і базу оподаткування, встановлено категорії платників податків, які мають право на податкову пільгу, у зв’язку із одержанням бюджетного гранту. Підкреслено, що на сьогодні податкові пільги стосуються тільки бюджетних грантів, що надаються Українським культурним фондом. У свою чергу, на підставі аналізу праць вчених з юридичних та економічних наук визначено перелік найпоширеніших у світовій практиці податкових пільг, які використовуються для стимулювання інноваційної діяльності. Окрему увагу приділено особливостям податкового стимулювання інноваційної діяльності у Польщі, Угорщині, Іспанії та Франції. Встановлено спільні риси та принципові відмінності між концепціями податково-правового стимулювання інноваційної діяльності в Україні та у зазначених країнах Європейського Союзу.
Keywords: budget grant; innovative activity; research and development; tax benefits; Ukrainian Startup Fund; бюджетний грант; інноваційна діяльність; науково-дослідні і дослідно-конструкторські роботи; податкові пільги; Фонд розвитку інновацій